Can Free Provision Reduce Demand for Public Services? Evidence from Kenyan Education - Bold, Tessa (World Bank, Washington, DC, 2014)
In 2003 Kenya abolished user fees in all government primary schools. Analysis of household survey data shows this policy contributed to a shift in demand away from free schools, where net enrollment stagnated after 2003, toward fee-charging private schools, where both enrollment and fee levels grew rapidly after 2003. These shifts had mixed distributional consequences. Enrollment by poorer households increased, but segregation between socio-economic groups also increased. The shift in demand toward private schooling was driven by more affluent households who (i) paid higher ex ante fees and thus experienced a larger reduction in school funding, and (ii) appear to have exited public schools partially in reaction to increased enrollment by poorer children.